Noether's Theorem and the Willmore Functional - Bernard, Yann (arXiv.org, 2014)
Noether's theorem and the invariances of the Willmore functional are used to derive conservation laws that are satisfied by the critical points of the Willmore energy subject to generic constraints. We recover in particular previous results independently obtained by R. Capovilla and J. Guven, and by T. Riviere. Several examples are considered in details.